Compliance with the Guide of Good Governance Practices and Quality of External Audit: Case of Listed Tunisian Companies in the Stock Exchange - Abidi, Ilyes; Touhami, Kamel (International Journal of Economics and Financial Issues, 2024)
The main objective of this study is to analyze the influence of corporate governance on the quality of external auditing within Tunisian companies listed on the stock exchange. This meticulous analysis aims to elucidate how adherence to the principles outlined in the Good Governance Practices Guide can impact and enhance the quality of external auditing. The results obtained using the System GMM model highlight the Guide’s ability to strengthen governance practices on a national scale, promote transparency, and ensure the proper functioning of businesses. Furthermore, they indicate a persistence of audit quality, suggesting that well-executed audit procedures, effective internal controls, and audit continuity can contribute to better audit quality. On the other hand, this research reveals a negative and significant relationship between indebtedness and the quality of external auditing, explained by financial pressures, transaction complexity, and risks to auditor independence in heavily indebted companies. Additionally, this research investigates the correlation between board composition and audit quality. Institutional and independent directors demonstrate a significant positive impact, attributed to their expertise, independence, and role in accountability and transparency. However, the nature of the activity, whether financial or non-financial, does not seem to influence the quality of external auditing, suggesting that auditors adhere to the same standards regardless of the sector.